Isolation of a freshwater cyanophage (F1) capable of infecting Anabaena flos-aquae and its potentials in the control of water bloom - Wu, Weizhong; Zhu, Qing; Liu, Xinyao; An, Chengcai; Wang, Jianlong (INTERNATIONAL JOURNAL OF ENVIRONMENT AND POLLUTION, 2009)
A cyanophage capable of infecting Anabaena floaquae was isolated by traditional dilution and plating techniques from a eutrophicated freshwater lake, Dianchi Lake, in Yunnan Province, China, and designated as F1. Morphologically, cyanophage F1 is similar to the bacteriophage T4, and it should belong to Myoviridae. Cyanophage F1 could effectively lyses Anabaena flosaquae cells both on the cyanobacterium plates and in liquid cultures. In microcosm experiments, inoculation of cyanophage F1 could clear the artificial Anabaena flosaqua water blooms within three days. The results could provide important information on the cyanobacterial/phage interactions in the field, and suggested that cyanophage F1 could be a promising bio-control agent in the control of cyanobacterial blooms.